Gameful Second and Foreign Language Teaching and Learning Theory, Research, and Practice - Reinhardt, Jonathon (New Language Learning and Teaching Environments, 2019)
This book offers a comprehensive examination of the theory, research, and practice of the use of digital games in second and foreign language teaching and learning (L2TL). It explores how to harness the enthusiasm, engagement, and motivation that digital gaming can inspire by adopting a gameful L2TL approach that encompasses game-enhanced, game-informed, and game-based practice. The first part of the book situates gameful L2TL in the global practices of informal learnful L2 gaming and in the theories of play and games which are then applied throughout the discussion of gameful L2TL practice that follows. This includes analysis of practices of digital game-enhanced L2TL design (the use of vernacular, commercial games), game-informed L2TL design (gamification and the general application of gameful principles to L2 pedagogy), and game-based L2TL design (the creation of digital games purposed for L2 learning). Designed as a guide for researchers and teachers, the book also offers fresh insights for scholars of applied linguistics, second language acquisition, L2 pedagogy, computer-assisted language learning (CALL), game studies, and game design that will open pathways to future developments in the field. Jonathon Reinhardt is Associate Professor of English Applied Linguistics and Second Language Acquisition and Teaching at the University of Arizona, USA. .